Bioinformation analysis of rotavirus vaccine efficiency - S. O. Soloviov; I. V. Dziublyk; V. V. Trokhymchuk (The State Expert Center of the Ministry of Health of Ukraine, 2019)
A couple of studies have shown that viruses cause from 25 to 60% of acute intestinal infections (AII) cases, among which rotaviruses play a leading role in the structure of children's AII of viral etiology. According to the WHO recommendations, vaccination against rotavirus infection should be included into national immunization programs. Due to a wide diversity of circulating rotavirus genotypes, the issue of RVI vaccine efficiency, taking into account the dynamics of the molecular-genetic spectrum of RVI pathogens over time, remains relevant. The aim of the work - мodeling the dynamics of the molecular genetic spectrum of RVI pathogens and bioinformation analysis of f rotavirus vaccine efficiency. The object of the analysis was the results of molecular and epidemiological studies of RVI in Kyiv, conducted from 2007 to 2015. The dynamics of the genotypic spectrum was modeled using a Markov model, which involved replacing shares of the molecular genetic spectrum of rotaviruses with others ones according to homology with the vaccine strain: homology in both G and P genotypes, homology in G genotype or P genotype, no homology in both G and P genotypes. The method of rotavirus vaccine efficiency evaluation is based on data from clinical observations of vaccine efficiency, where different degrees of its efficiency against severe gastroenteritis caused by rotaviruses with different genotypes were shown. The shares of each genotype group in the general circulation of genotypes were taken as weights of the degree of homology relative to the vaccine strain, and the effectiveness of the vaccine against the strains of a specific homology group was obtained from clinical observations. The results of the analysis based on the constructed distribution curves of the molecular genetic spectrum of rotaviruses due to rotavirus vaccine strain homology in Kiev showed that, despite the observed dynamics of the molecular genetic spectrum of RVI pathogens, the expected genotype-specific efficiency of rotavirus vaccine would be constant with a value of 0.835 or 83.5% against rotavirus gastroenteritis with a Vesikari severity of > 11 points. It was proposed mathematical model for prediction of molecular genetic spectrum of rotaviruses dynamics, taking into account the homology of the genotypes of RVI pathogens with respect to the vaccine strain. According to the literature data of molecular and epidemiological studies of rotaviruses in Kyiv, the parameters of the proposed mathematical model and the dynamics of the molecular genetic spectrum of RVI pathogens were determined. Using mathematical modeling, the expected genotype-specific efficiency of the rotavirus vaccine was determined based on Kyiv regional retrospective molecular and epidemiological data.